(3efbhd ef GdCQHYjfs - (3eMeO Hf YeQ Hf GdMSf Hf GdMSjf GdJjej GdHcQj, CHh YHO Gddg, aNQ GdOjf GdQGRqj,J (B606 (3g` s
(3ChdgG (B:s
(3hGMJL GdTQja GdeQJVi QVi Gddg Yfg Ydi Gfg jLH Ydi Gddg JYGdi fUH GdEeGe HCf bGd (B:" (3fUH GdEeGe dWa hGddWa hGLH Ydi Gddg JYGdi s
(3BNQgG (B:s
(3ade jcf ddWa ajg CKQ GdHJg dcf dGfSde Cf GddWa hGLH hbO bOefG eG jOd Ydi Gfg dG jLH Ydi Gddg JYGdi TF CUdkG agPG gh GdcdGe GdeNJUQ ai gPG GdHGH hGddg Gdehab s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYeI (B_ (3GdfLa (B(369) s
Keywords: (3GdeLGejYs